Current concepts in gene therapy of the musculoskeletal system - Ivković, A; Pascher, A; Hudetz, D; Jelić, M; Haspl, M; Windhager, R; Pećina, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2006)
The purpose of this article is to review the remarkable progress in the field of musculoskeletal system gene therapy. Since the introduction of this concept 15 years much of the preclinical and clinical data have emerged. The original target, rheumatoid arthritis, has been subjected to clinical phase II efficacy protocol, and osteoarthritis gene therapy efficacy is being thoroughly investigated in various animal models. The most promising area of research in this field however, is the tissue repair, because it doesn't require prolonged period of gene expression, local delivery is reasonably simple and it avoids substantial risk associated with systemic delivery, and levels of gene expression don't need to be so finely regulated. Gene transfer is successfully being used to aid the repair and regeneration of bone, cartilage, ligament tendon, meniscus and intervertebral disc. Other potential applications of gene therapy in musculoskeletal system include osteoporosis, aseptic loosening, genetic diseases and tumors. Highly encouraging data gained from these studies have confirmed that gene therapy is a promising therapeutic solution to treat various musculoskeletal system disorders.
Keywords: Growth Substances; genetická terapie; Genetic Vectors; růstové látky; muskuloskeletální nemoci; Genetic Therapy; genetické vektory; Humans; Musculoskeletal Diseases; lidé